Ahmed valve drainage implant surgery in the management of paediatric aphakic glaucoma. Issue 7 (17th June 2005) - Kirwan, C; O'Keefe, M; Lanigan, B; Mahmood, U
Abstract : Background: Paediatric aphakic glaucoma presents months or years after cataract surgery in children and is a major long term complication. The results of surgical treatment are poor and many children require multiple and repeat procedures with poor visual outcomes. Methods: 13 children (19 eyes) had Ahmed valve implantation surgery, nine of the children had previous procedures such as cycloablation or trabeculectomy. Mitomycin was used at surgery in some patients and valve needling with Healon GV and 5-fluorouracil in some blebs after surgery. SF6 gas was also used at the time of surgery in most children to reform the anterior chamber. Results: 12 of the children (18 eyes) achieved intraocular pressure control of 15 mm Hg or less with a valve alone or with additional medical therapy. Conclusion: Ahmed valve implantation surgery alone or in combination with medical therapy is successful and safe in the management of paediatric aphakic glaucoma.